Dynamics of clinical parameters after cystectomy using electric welding of the edges of the operated area in patients with odontogenic cysts of the jaws - Chepyshko Світлана Іллівна; Maksymiv Олег Олегович (Actual Dentistry, 2022)
Goal. To evaluate the effectiveness of the proposed method of cystectomy using electric welding on the basis of the obtained clinical and biochemical parameters. Materials and methods. Cystectomy was performed in 87 patients: 20 patients – 1 control group (classical surgical method), 28 patients – 2 control groups (cystectomy using laser technology) and 39 patients – the main group (cystectomy using electric welding). Results. The use of electric welding technology during cystectomy allowed to reduce and facilitate the postoperative period in patients of the main group up to 5 days in contrast to patients in other groups, in which symptoms of inflammation and pain were observed up to 14 days. Conclusions. The use of electric welding of tissues during cystectomy in the oral cavity allowed to achieve sterility of the operated area, reduce the intervention time, and due to the absence of foreign bodies in the wound to reduce and facilitate postoperative rehabilitation of patients.